Early morpho-physiological response of oilseed rape under seed applied Sedaxane fungicide and Rhizoctonia solani pressure - Panozzo, Anna; Barion, Giuseppe; Moore, Selina Sterup; Cobalchin, Francesca; Di Stefano, Alberto; Sella, Luca; Vamerali, Teofilo (Frontiers in Plant Science, 2023)
The SDHI fungicide Sedaxane has shown to efficiently control Rhizoctonia spp. growth and to possess biostimulant properties in cereal crops. As a first, the present study investigated its effectiveness as a seed treatment of the dicot species oilseed rape (Brassica napus var. oleifera). For this, seeds were treated with different fungicides (i) the conventionally used active ingredient Thiram, (ii) Sedaxane, (iii) Sedaxane in combination with Fludioxonil and Metalaxyl-M and later sown in soil inoculated with Rhizoctonia solani. The resulting shoot and root growth from the treated seeds were recorded in early growth stages and the presence of Rhizoctonia DNA in the basal stem tissue was quantified. Here we demonstrate that all the fungicide treatments were effective in greatly reducing the presence of Rhizoctonia DNA, with Thiram confirming to have high fungicidal effects. Following seed treatment, shoot and root growth at the 2-leaf stage was reduced regardless of inoculation, indicating that the fungicides became phytotoxic, with particular respect to Thiram. In seedlings grown in inoculated soil, significant biostimulation of the roots was observed at the 4-leaf stage of treatments containing both Sedaxane alone and in a mixture. Leaf area was stimulated in control soil not inoculated with Rhizoctonia likely due to improved PSII efficiency, stomatal conductance and CO2 assimilation rate. Young oilseed rape seedlings are thus highly sensitive to seed treatments with these fungicides, and in particular to Thiram. The retardation in growth is quickly overcome by the 4-leaf stage however. We confirm that Sedaxane indeed possesses root biostimulant properties in oilseed rape, which are enhanced in combination with other fungicides. Such biostimulating properties impose its greatest effects under conditions of biotic stress.